Modeling Pension Reform : The World Bank's Pension Reform Options Simulation Toolkit - World Bank (Washington, DC, 2012)
Today's pension policies can affect retirement incomes and the public finances for decades to come. Retirement income systems that are affordable today, will often prove unsustainable in the future, given the twin pressures of demographic aging and the maturing of pension schemes. The World Bank's pension reform options simulation toolkit (PROST) models pension contributions, entitlements, system revenues, and system expenditures over a long time frame. The model is designed to promote informed policymaking, bridging the gap between quantitative and qualitative analysis of pension regimes. It is a flexible, computer-based toolkit, easily adapted to wide range of countries' circumstances.